Strategy For Developing Catfish Maintenance Residents of The Hill Lebaksari Subdistrict Baureno Regency Bojonegoro - Ahmad Rifai; Maftuch; Nurul Badriyah; Dini Atikawati (Postgraduate, University of Mataram, 2025)
Fishery catches are a vital food source in Indonesia, including catfish, which is a key freshwater species cultivated commercially, particularly on Java. This study examines the current state of catfish farming in Lebaksari Hamlet, Bojonegoro Regency, East Java, and proposes development strategies based on socio-economic aspects. Employing a quantitative descriptive approach, the research assesses the social and economic impacts of catfish farming on local residents. Data were collected from 30 catfish farmers selected through Simple Random Sampling, covering aspects from rearing to marketing. SWOT analysis was used for data interpretation. The findings indicate that leveraging existing strengths and seizing opportunities, such as market expansion and technological advancements, can enhance catfish farming development. Key strategies include market development, optimizing farming technology, fostering partnerships with customers and business partners, sustainable natural resource utilization, and strengthening collaboration with government bodies. These strategies aim to improve productivity, economic benefits, and sustainability in catfish farming in Lebaksari Hamlet.